2005
DOI: 10.1158/0008-5472.can-04-4014
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase-1 Could Facilitate the Religation of Topoisomerase I-linked DNA Inhibited by Camptothecin

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is known to have an important role in camptothecin sensitivity and interacts with topoisomerase I. In the present study, the impact of PARP-1 on the topoisomerase I-DNA complex stabilized by camptothecin was assessed. It was shown that NH 2 terminustruncated topoisomerase I (amino acids 201-765) showed at least 4-fold less sensitivity to camptothecin than full-length topoisomerase I in the oligonucleotide religation assay. PARP-1 could prevent the action of camptothecin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
(45 reference statements)
2
28
0
Order By: Relevance
“…Previous experiments using purified proteins under cell-free conditions demonstrated a potential role for pADPr generated by PARP1 in the modulation of topo I activity (33)(34)(35)(36)(37). These experiments predicted that PARP inhibition would alter the kinetics of topo I-mediated strand religation, thereby shifting the cleavage-religation equilibrium (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous experiments using purified proteins under cell-free conditions demonstrated a potential role for pADPr generated by PARP1 in the modulation of topo I activity (33)(34)(35)(36)(37). These experiments predicted that PARP inhibition would alter the kinetics of topo I-mediated strand religation, thereby shifting the cleavage-religation equilibrium (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…3E, third panel) (33)(34)(35)(36)(37). This model would predict that increased Topo1cc covalent complexes would be formed in the presence of PARP inhibitors.…”
Section: Parp Inhibition Does Not Directly Alter the Cell Cycle Topomentioning
confidence: 99%
See 1 more Smart Citation
“…9C) compared with interphase cells. Although the ability of phosphorylation in the N-terminal domain to affect events at the topo I active site might seem counterintuitive, previous studies have demonstrated that removal of the N-terminal domain modestly decreases topo I enzymatic activity and CPT sensitivity (47,48). Crystallization of topo I with an intact N terminus, a feat that has not been reported to date, appears to be required to determine whether phosphorylation of Ser 21 enhances activity and CPT sensitivity through an interaction with portions of the N-terminal domain previously implicated in topo I activation or through interaction with different regions of the polypeptide.…”
mentioning
confidence: 99%
“…Top1 ubiquitination and subsequent degradation by the 26 S proteasome (48) have been suggested as an early step in the repair of Top1cc prior to tyrosyl-DNA phosphodiesterase (Tdp1) action (49). PARP-1 also binds to the N-terminal of Top1 and facilitates the religation of Top1cc (50). It is therefore plausible that the caspase-3-dependent cleavage of Top1 serves to prevent the repair of Top1cc during apoptosis.…”
Section: Caspase-3-cleaved Top1 Is Preferentially Involved In the Apomentioning
confidence: 99%